The Use of Artificial Intelligence Technology in Understanding Media and Business Content to Increase People's Digital Literacy - Firman Matiinu Sigit (International Journal of Technology and Education Research, 2024)
This research aims to describe the use of artificial intelligence technology in understanding media and business content to increase people's digital literacy. The research approach applied in this study is a qualitative approach using the literature study method. The data collection method used is documentation techniques, where data is collected from various library sources that are relevant to the research theme. The research instruments used are various bibliographic sources, such as books, journals, articles, bibliography, and so on. The research results show that the presence of Artificial Intelligence in the digital marketing realm, especially content creation, is very useful for developing ideas through to their execution. Even so, humans are still needed when wanting to run Artificial Intelligence. Artificial Intelligence technology can be utilized to drive efficiency, innovation and strategic advantage. This involves understanding how Artificial Intelligence can be used in areas such as customer service, marketing, human resources, supply chain management and decision making. In the era towards Society 5.0 which is filled with technological innovation for the purpose of human welfare, we are witnessing surprising and sometimes very unexpected changes in various fields, including literacy.